Des strates sous la carte : les paradoxes de la surface dans A Week on the Concord and Merrimack Rivers de Henry D. Thoreau - Julien Nègre (Transatlantica, 2015)
Is Thoreau a reader of surface or of depth? In A Week on the Concord and Merrimack Rivers (1849), Thoreau describes his excursion on the river as a spatial experience of surface but he also evokes the longer perspective of deep time, which suggests an affinity with spatial and temporal depth. By looking at a hand-drawn map that Thoreau copied for the excursion, this article examines how Thoreau’s narrative is embedded in several different temporalities and how the spatial experience of surface becomes a temporal experience of depth, dramatized by language itself.